1999
DOI: 10.1021/jp9844361
|View full text |Cite
|
Sign up to set email alerts
|

Intracluster Ion−Molecule Reactions of Dimer Cations of Phenylsilanes

Abstract: Intracluster ion−molecule reactions of dimer cations of various phenylsilanes were investigated in order to elucidate reaction mechanisms of phenylsilane cation reported in the gas-phase FT-ICR study. Two types of reactions, SiR3 elimination and transfer, were observed. In the latter case, our observation strongly supported that a precursor of the reaction has a π-type complex configuration, [C6H6·SiR2]+, which has been proposed before. On the contrary, in the former case, a dimer cation forms a reaction int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…22 000 cm -1 , which corresponds to the local excitation (LE) band of the dimer cation. 2 It is evident that the ion signal intensities of both the products are reduced compared to that of the dissociation product. The results represent that the yield of the photoinduced intracluster reactions substantially depend on the photon energy for the excitation of the dimer ion.…”
Section: Resultsmentioning
confidence: 98%
“…22 000 cm -1 , which corresponds to the local excitation (LE) band of the dimer cation. 2 It is evident that the ion signal intensities of both the products are reduced compared to that of the dissociation product. The results represent that the yield of the photoinduced intracluster reactions substantially depend on the photon energy for the excitation of the dimer ion.…”
Section: Resultsmentioning
confidence: 98%
“…The reactions of diethylsilicenium ions, (C 2 H 5 ) 2 SiH , with benzene were studied by Kochina et al 83 using the radiolytic method. Intracluster ion^molecule reactions of various phenylsilane dimer cations were studied by Ishikawa et al 84 Two types of reactions, SiR 3 elimination and SiR 2 transfer, were observed within the clusters. Finally, in a series of studies, Antoniotti and co-workers 85,86 have studied the formation of compounds containing both silicon and carbon atoms from the ionization of the following mixtures in an ion trap: (SiH 4 C 2 H 4 ), 85 (SiH 4 C 3 H 6 ), 86 (SiH 4 C 2 H 6 ) and (SiH 4 C 2 H 2 ).…”
mentioning
confidence: 99%